The scientific school of Professor Volodymyr Sokovich (1874 - 1953) – the prerequisites for the creation, formation, development, modernity - O. R. Fesovets (History of science and technology, 2018)
The article gives an overview on the activities of the first dean of the operational faculty of the Moscow Institute of Railway Transport Engineers Volodymyr Sokovych, as the founder of the national scientific school "Organization of Railway Transportation" The fundamental publications for the new scientific discipline of the professor's publication are analyzed, the theoretical direc-tions of searches for his outstanding students are covered and the present state of the above-mentioned scientific school is shown.